Real-Time Character Matching Using Brute Force Algorithm in Typing Game-Based Learning - Rio Andriyat Krisdiawan; Rifky Putra Pratama; Nida Amalia Asikin (METIK Jurnal, 2026)
Typing skills are an essential component of digital literacy; however, conventional typing practice methods tend to be less engaging, which negatively affects students’ motivation and typing accuracy. This study aims to design and implement a computer-based typing game–based learning system that applies the Brute Force algorithm as a real-time character matching mechanism. The system was developed using the Game Development Life Cycle (GDLC) method, which consists of the initiation, pre-production, production, testing, and release phases. The Brute Force algorithm is employed to validate the correspondence between user input and the target words displayed in the game by sequentially comparing each character. System evaluation was conducted through functional testing, algorithm performance analysis, and a User Acceptance Test (UAT) involving teachers and students. The results indicate that the Brute Force algorithm achieves high character matching accuracy, deterministic behavior, and fast response time for relatively short word lengths. The time complexity analysis demonstrates a linear pattern O(n), while still satisfying real-time feedback requirements in educational games. Furthermore, the UAT results show a high level of user acceptance, indicating that the system is stable, consistent, and feasible as a game-based typing practice medium. Therefore, the Brute Force algorithm is proven to be suitable for implementation in typing game–based learning, particularly for basic to intermediate learning scenarios.